Environmental Literacy of Senior High School Students on Ornamental Plant Maintenance in Serang City, Indonesia - Alfira Laila Nurfadillah; Indah Juwita Sari; Nisah Afifah (Jurnal Pendidikan Indonesia Gemilang, 2024)
This study aimed to analyze students' environmental literacy by measuring the level of environmental literacy in the process of maintaining ornamental plants at school. The measured environmental literacy relates to students' knowledge, attitudes, and behavior in ornamental plant maintenance activities at school. The location of this research is one of the high schools in Serang City, Indonesia. The method used in this research is the descriptive qualitative method. Sampling was done by random sampling technique with a total sample of 30 students. Data collection techniques were carried out by conducting observations, interviews, and distributing an open-ended questionnaire consisting of 20 questions from the environmental literacy component derived from the modified MSELI instrument. The results showed that the average score of the knowledge component was 43.3 (high), cognitive skills 40 (medium), attitudes 34.6 (medium), and behavior 20.6 (low). Based on the results, it can be concluded that high school students obtained an environmental literacy score of 107.5 (medium) with the lowest score on the behavior component so environmental literacy needs to be improved.